Association of fruits, vegetables, and fiber intake with COVID-19 severity and symptoms in hospitalized patients: A cross-sectional study - Tadbir Vajargah, Kiana; Zargarzadeh, Nikan; Ebrahimzadeh, Armin; Mousavi, Seyed Mohammad; Mobasheran, Parnia; Mokhtari, Pari; Rahban, Habib; Găman, Mihnea-Alexandru; Akhgarjand, Camellia; Taghizadeh, Mohsen; Milajerdi, Alireza (Frontiers in Nutrition, 2022)
Background and aims: Fruits and vegetables are rich in fiber and a good source of anti-inflammatory and immune-boosting vitamins, minerals, and antioxidants. We investigated the association between fruits, vegetables, and fiber intake and severity of COVID-19 and related symptoms in hospitalized patients. Methods: A total of 250 COVID-19 hospitalized patients aged 18 to 65 years were recruited for this cross-sectional study in Kashan, Iran, between June and September of 2021. Dietary intakes were assessed using an online validated 168-item food frequency questionnaire (FFQ). COVID-19 severity and symptoms were evaluated using the National Institutes of Health (NIH) COVID-19 Treatment Guidelines. Moreover, we examined COVID-19 symptoms, inflammatory biomarkers, and additional factors. Results: The mean age of participants was 44.1±12.1 years, and 46% had severe COVID-19. Patients with higher consumption of fruits (OR: 0.37; 95% CI: 0.17, 0.77, P-trend = 0.009), vegetables (OR: 0.34; 95% CI: 0.16, 0.72, P-trend = 0.005) and dietary fiber (OR: 0.30; 95% CI: 0.14, 0.62, P-trend = 0.002) had lower odds of having severe COVID-19. In addition, they had shorter hospitalization and convalescence periods, lower serum C-reactive protein (CRP), and a reduced risk of developing COVID-19 symptoms such as sore throat, nausea, and vomiting, dyspnea, myalgia, cough, weakness, fever, and chills. Conclusion: Higher consumption of fruits, vegetables, and fiber was inversely linked with COVID-19 severity, clinical symptoms, hospitalization and convalescence duration, and CRP concentrations. The results should be interpreted with caution in light of the limitations, and prospective cohort studies are required to further evaluate these findings.